Cutaneous siderosis after intramuscular iron injections: a case report. (December 2014) - Ozlu, Emin; Karadag, Ayse Serap; Bilgili, Serap Gunes; Bayram, Irfan
Abstract Skin reactions against injected or implanted foreign materials are not rare. Siderosis is a disease characterized by the accumulation of iron in various tissues. Brownish-gray discoloration of the skin can be seen as a side-effect on the injection area after the parenteral iron treatment. Here, we present cutaneous siderosis case developed after multiple intramuscular iron injection on the gluteal region for iron-deficiency anemia. Development of cutaneous siderosis after intramuscular iron injection rarely has been reported in the literature before.